Crimes against humanity climate change and Trump's legacy of planetary destruction - Blau, Judith (Routledge, 2019)
Judith Blau is a sociologist who has written extensively on human rights and recently on cilmate change. In her new book she develops the idea that protecting everyone's human rights and slowing planetary warming are the same goals. It is now clear that the leader of the richest, most powerful country in the world - United States President Donald J. Trump - has set the trigger of destruction by exempting the United States from the international treaty that aims to give the entire planet some reprieve from warming - that is, all countries of the world have entered into an agreement to end reliance on fossil fuels except the united States, which withdrew at the outset of the Trump Administration. Regardless of the U.S. position in the future, the country's emissions are so very extremely high that they will continue to wreck havoc on the entire world. While Blau maintains that President trump has committed a crime against humanity, even beyond his tenure the book sets the stage for a human rights approach to climate change for the future.